Využití Petriho sítí pro varianty nakládání s biologicky odbouratelným komunálním odpadem - Baťa, Robert; Obršálová, Ilona; Volek, Josef; Jordaõ, Ticiano Costa (Univerzita Pardubice, 2008)
Biologically degradable component of municipal waste has its legislative, economic, environmental and social context. In recent years, various possibilities of separation, logistics and collection with technical alternatives of these material flows solutions have been focused. The paper presents the possibility to use modelling with the help of Petri nets with the aim to find a solution which would minimize the impact on environment and maximize utilization of this component of municipal waste.
Keywords: municipal waste; biodegradability; bio-waste; Petri Nets; environmental impacts; Modelling